What's in a name? Choosing a title for a female pelvic medicine and reconstructive surgery clinic: A prospective questionnaire. Issue 1 (2nd October 2019) - Nguyen, Anh; Cheung, Alice; Berg, William; Lee, Wai; Weissbart, Steven; Kim, Jason
Abstract: Aims: A new multidisciplinary clinic specializing in female pelvic medicine and reconstructive surgery (FPMRS) opened at our institution. We sought to assess patient preference in naming this new center, and how readability and word choice informs these preferences. Methods: We prospectively surveyed patient preference in naming this new center, as well as patient knowledge and societal perception of pelvic floor disorders. This survey was distributed to female patients presenting to general urology and gynecology clinics. Results: There were 300 respondents out of 1000 distributed surveys. Patients preferred titles with accessible readability scores and societally neutral vocabulary. Preferred titles for the clinic were at a 6th‐grade readability level. Patients preferred neutral titles that included the word "health" and disliked titles that contained the words "pelvic floor" and "dysfunction." In general, survey participants believed that "incontinence" was associated with negative connotations. Conclusion: Readable and neutral vocabulary in the title of the clinic are key components of patient‐preferred titles for an FPMRS clinic and affect patient comfort levels in scheduling an appointment.